Underrepresentation of African American Female Senior Administrators in Southeastern Colleges and Universities in the US - Curtis, Annie LaToya (My University, 2022)
This research investigated four African American females’ comprehension of their life and career trajectories in senior administration jobs. I explored how the race and social status of women influences and shape their leadership roles as practicing female senior administrators. This study highlights the women’s efforts to excel with a focus on the influence of their race and gender as senior administrators. Based on the literature review, I outlined some of the main trends of the intersection of race and gender in female senior leadership. The analytical framework used to frame the data comprised four conceptual strands: 1) advisors and mentors, 2) increasing visibility in the work place, 3) Black Tax, and 4) beating the odds. The findings suggest that African American senior administrators will likely succeed because they devised survival strategies to help them overcome racial and misogynistic challenges in America. The data revealed the women’s struggles to stay visible and essential. Through the study, I demonstrated that African American women’s leadership isn’t just about their strength and resilience. It is about how consistently they rise to overcome challenges for the good of all. The data from the participants show the strategies to address the social, political, and economic challenges they face being Black and female in White male-dominated spaces. I describe the nature and type of research that can raise awareness of the need to level the playing field for African American women in leadership, which can form the basis of further research. My study was based on data collected from African American female senior administrators. Future studies need to extend the database by studying other stakeholders involved in administration: White male and female leaders and Black male leaders to broaden the context. Keywords: African American, Female, Senior Administrators, Leadership, Race, Social Status
Chapter I: INTRODUCTION 1 -- Statement of the Problem 2 -- Purpose 3 -- Research Questions 3 -- Study Significance 3 -- Conceptual Framework 4 -- Summary of Methedology 6 -- Limitations 6 -- Chapter Summary 6 -- Definition of Terms 7 -- Chapter II: REVIEW OF LITERATURE 10 -- Literature Search Strategy 11 -- Conceptual Framework 12 -- Literature Review Related to Key Variables and/or Concepts 14 -- African American Women in Higher Education 14 -- Barriers of African American Females on the Path to and in Senior-Level Administration 15 -- Institutionalized Racism 17 -- Discriminatory Hiring Practices 19 -- Discriminatory Granting Of Tenure 20 -- Discrimination Of The Concrete Ceiling 21 -- The Impact Of Intersectionality 22 -- The Impact of Social Perception of African American Women in Leadership 23 -- Women’s Perspective Skewed by the Impact of Social Perception 25 -- Identity Shifting and Role Incongruity 27 -- Life and Career Experiences of African American Females Seeking and in Senior-Level Administration 28 -- Strategies Utilized to Improve Opportunities for African American Females in Senior-Level Administration 32 -- Recognizing The Value Of Minority Representation In Student Outcomes 39 -- The Role of Mentorship 40 -- Summary and Conclusions 41 -- Chapter III: METHODOLOGY 45 -- Overview 45 -- Research Design 45 -- Site Selection and Description 46 -- Participants 47 -- Instrumentation 48 -- Data Collection 49 -- Data Analysis 51 -- Validity 52 -- Credibility 54 -- Conformability 55 -- Dependability 55 -- Transferability 55 -- Ethical Considerations 55 -- Summary 56 -- Chapter IV: Participant Profiles 57 -- Chapter V: Themes 120 -- Chapter VI: Discussion and Conclusion 165 -- References: 186
Keywords: African American women college students; African American women; Dissertations, Academic--United States; Leadership in women; Leadership; Education; Racism; Sexism